The Mediating Role of Supply Chain Capability in Customer Integration and Operational Performance: JEL Classification: M11, L25, L83, M31 - Abidatul Ulya; Muhammad Hamdi; Aftoni Sutanto; Zaki Amirul Amri; Dini Andriani; Muhammad Iqbal Fauzi (Journal of Management and Administration Provision, 2026)
The purpose of this study was to examine the mediating role of supply chain capability in the micro-café industry in the Special Region of Yogyakarta on the influence of customer integration on operational performance. This study used a quantitative approach with a survey method, with 154 respondents who were both customers and employees of the café business. Data were collected using a structured questionnaire and analyzed using a causal relationship modeling approach based on latent variables to examine the long-term and short-term effects between variables. The results of this study indicate that customer integration influences operational performance. Furthermore, supply chain capability have been shown to have a positive impact on operational performance and serve as a mediator in the relationship between customer integration and operational performance. This indicates that collaboration and customer information exchange influence operational efficiency and accuracy. This study concludes that customer integration, supported by strong supply chain skills, has a positive impact on the operational performance of small and medium enterprises. This impact is reflected in the increased ability of business actors to efficiently manage the flow of goods, information, and resources, thereby optimally improving operational performance.